Metallurgical characterization of experimental Ag-based soldering alloys - Argyro Ntasi; Youssef S. Al Jabbari; Nick Silikas; Sara M. Al Taweel; Spiros Zinelis (Saudi Dental Journal)
Aim: To characterize microstructure, hardness and thermal properties of experimental Ag-based soldering alloys for dental applications. Materials and methods: Ag12Ga (AgGa) and Ag10Ga5Sn (AgGaSn) were fabricated by induction melting. Six samples were prepared for each alloy and microstructure, hardness and their melting range were determined by, scanning electron microscopy, energy dispersive X-ray (EDX) microanalysis, X-ray diffraction (XRD), Vickers hardness testing and differential scanning calorimetry (DSC). Results: Both alloys demonstrated a gross dendritic microstructure while according to XRD results both materials consisted predominately of a Ag-rich face centered cubic phase The hardness of AgGa (61 ± 2) was statistically lower than that of AgGaSn (84 ± 2) while the alloys tested showed similar melting range of 627–762 °C for AgGa and 631–756 °C for AgGaSn. Conclusion: The experimental alloys tested demonstrated similar microstructures and melting ranges. Ga and Sn might be used as alternative to Cu and Zn to modify the selected properties of Ag based soldering alloys. Keywords: Soldering, Ag-based alloys, Microstructure, DSC, SEM, EDX, XRD